Cognitive functioning and subjective quality of life in relapsing-remitting multiple sclerosis patients before and after percutaneous transluminal angioplasty: a preliminary report - De Pasquale, Concetta (Dove Medical Press, 2014)
BACKGROUND: Multiple sclerosis (MS) is a disease of the nervous system that has profound effects on everyday functioning and quality of life of not only the person who is diagnosed, but also her/his family and acquaintances. Despite this, the uncertainties of the actual etiological basis of MS make it difficult to reach a conclusive statement about the optimal therapeutic management of the disease, which may differ depending on the given case and phase of illness. This has led to an interest in potential novel therapeutic avenues, including percutaneous transluminal angioplasty (PTA). Yet, evidence in support of PTA in the management of MS is scarce and contradictory. The aim of the present study was to provide a preliminary assessment as to whether PTA may impact subjective quality of life and cognitive functioning in severe MS. METHOD: Ninety-five MS outpatients were followed-up for 24 months on a scheduled basis using the Milan Overall Dementia Assessment and the short-form 36-item scales, and were clinically evaluated by an appointed neurologist and psychiatrist. RESULTS: At end point (month 24), only a minority of patients were still active in the study (n=33 or 34.74%). Among other measures, those who remained in the study until completion showed a significantly better Expanded Disability Status Scale and Milan Overall Dementia Assessment autonomy profile at study entrance compared to those patients who did not remain in the study until completion. Limitations were: a lack of any active control group; small sample size; Berkson’s bias; and selection by indication biases. CONCLUSION: Given the burden of MS and its high attrition rate, additional studies, including bigger samples, active control groups, and Cox’s regression and survival analysis in case of randomization, should shed further light on the actual usefulness of PTA for the most severe cases of MS.